2014
DOI: 10.3109/14647273.2014.927595
|View full text |Cite
|
Sign up to set email alerts
|

Oral antioxidants supplementation for women with unexplained infertility undergoing ICSI/IVF: Randomized controlled trial

Abstract: Oral antioxidants in the form of a combination of multivitamins and minerals (amino acid chelated) did not improve oocyte quality and pregnancy rates in women with unexplained infertility undergoing IVF/ICSI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…A study carried out in women undergoing IVF showed that, vitamin E present in the follicular fluid or serum, is related to higher oocyte maturation and higher quality embryos rates [ 123 ]. In particular, 0.35/1 mg/dL and 1.5/2 mg/dL are the levels of vitamin E in follicular fluid that allowed achieving the highest percentage of MII oocytes [ 123 ]. Similarly, 10/15 mg/dL serum level of vitamin E was related to the highest percentage of higher quality of embryos obtained [ 123 ].…”
Section: Agents Consideredmentioning
confidence: 99%
“…A study carried out in women undergoing IVF showed that, vitamin E present in the follicular fluid or serum, is related to higher oocyte maturation and higher quality embryos rates [ 123 ]. In particular, 0.35/1 mg/dL and 1.5/2 mg/dL are the levels of vitamin E in follicular fluid that allowed achieving the highest percentage of MII oocytes [ 123 ]. Similarly, 10/15 mg/dL serum level of vitamin E was related to the highest percentage of higher quality of embryos obtained [ 123 ].…”
Section: Agents Consideredmentioning
confidence: 99%
“…This finding is in agreement with the results of our study. Youssef et al used antioxidant preparations containing vitamins A, C, and E, zinc, molybdenum, selenium, biotin, and bioflavonoids in unexplained infertility groups; these groups showed no difference in clinical pregnancy rates [21]. Despite the similar patient group, the significant increase in clinical pregnancy rates revealed in the current study may be due to the fact that CoQ10 is not only an antioxidant but also an agent that increases mitochondrial energy production.…”
Section: Discussionmentioning
confidence: 39%
“…This study was carried out on 299 patients with unexplained infertility between 21 DHA 230 mg; TAB, Turkey) for two months before ovarian stimulation. These were registered as the subject group, while 164 patients who did not take the supplement were evaluated as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, there are some trials that failed to report this beneficial effect of oral antioxidant supplementation in the treatment of female infertility. In a study by Youssef et al [36], oral antioxidants in the form of a combination of multivitamins and minerals did not improve oocyte quality and pregnancy rates in women with unexplained infertility undergoing IVF/ICSI treatment. The lack of significant differences between the study and control groups could be explained by a lack of follicular fluid antioxidants during in vitro fertilization that may disturb the oxidant-antioxidant balance, rendering the culture media less protected against oxidation.…”
Section: Discussionmentioning
confidence: 92%